Renal tuberculosis in an imatinib-treated chronic myeloid leukemia - Abhilash Chandra; Namrata Rao; Kiran Preet Malhotra (Brazilian Journal of Nephrology, 2020)
ABSTRACT Imatinib, which inhibits tyrosine kinase activity of Bcr-Abl protein, is a standard form of treatment for chronic myeloid leukemia (CML). Through its immunomodulatory effect it affects T cell function in a number of ways. It inhibits antigen-induced T cell activation and proliferation. Antigen-specific T-cells and macrophages are vital for protection against Mycobacterium tuberculosis. Here we present a case of renal tuberculosis associated with imatinib therapy in the maintenance phase of CML. With granulomatous interstitial nephritis and positive tubercular DNA on renal biopsy, the condition was successfully treated with anti-tubercular therapy. This case provides support to the hypothesis that imatinib therapy in CML increases the susceptibility to tuberculosis and strict vigilance is required to enable its early detection and treatment.